Discursive Construction of Digital Economy and Identity in TikTok Live (A Critical Discourse Analysis of Live Tiktok @Hepibor86) - Paramita, Fransisca Benedicta Avira Citra (Communica : Journal of Communication, 2026)
This study aims to analyse the discursive constructions of the digital economy and community identity within the Joged Sadbor phenomenon on the TikTok live streams of the @Hepibor86 account. The study employs a qualitative approach using Norman Fairclough’s Critical Discourse Analysis. The research corpus consists of publicly accessible TikTok live stream material from January to March 2026, including live clips, five selected screenshots, screen recordings, and traces of audience interaction in the form of comments and virtual gifts. The dataset was purposively limited based on the involvement of community groups in the broadcasts, the intensity of digital economic interactions, the emergence of jargon and recurring communication patterns, and the representation of performance practices relevant to the research focus. Analysis was conducted across three dimensions—text, discursive practices, and social practices—to examine language choices, performance patterns, mechanisms of content production and consumption, and their relationship to the platform’s economic logic. The research findings indicate that Joged Sadbor functions not only as entertainment and a source of additional income, but also as a space for the negotiation of local identity, digital visibility, and collective performativity. The findings also reveal practices of the commodification of the body, entertainment, and empathy, where expressions of local culture are repeatedly displayed to attract the audience’s attention and secure gifts as economic value. Therefore, this phenomenon does not simply supplant traditional cultural values, but rather reflects a shift in meaning, an adaptation of cultural practices, and the monetization of local expressions within TikTok’s attention economy.